DOP40 Comorbidities and epidemiological risk factor but not immunosuppressive therapies increase the risk of COVID-19 in Inflammatory Bowel Disease (IBD): An ENEIDA-based, case-control study. (27th May 2021) - Zabana Abdo, Y; Marín-Jiménez, I; Rodríguez-Lago, I; Vera, I; Martín, M D; Guerra, I; Gisbert, J P; Mesonero, F; Benítez, O; Taxonera, C; Ponferrada-Díaz, Á; Piqueras, M; et al.
Abstract: Background: The information regarding IBD patients with COVID-19 suggests that the factors related to bad outcome are older age and comorbidity whereas immunosuppressants do not have a significant impact worsening the disease evolution. To date, there is no information to assess if there are differences in epidemiological, demographical, and clinical characteristics between infected and non-infected IBD patients. Methods: Case-control study in IBD patients with COVID-19 (cases) compared to IBD without COVID-19 (controls) in the period March-July/2020 within the ENEIDA registry (promoted by GETECCU and with more than 60.000 IBD patients included). Cases were matched 1:2 by age (±5y), type of disease (CD/UC), gender, and centre. All controls were selected from only one investigator blind to other clinical characteristics of the patients to avoid selection bias. Results: 496 cases and 964 controls from 63 Spanish centres were included. No differences were found within the basal characteristics including CD location, CD behaviour, extraintestinal manifestations, family history of IBD or smoking habits. Cases had ≥ 1 comorbidities (cases:43%vs. controls:36%, p =0.01) and occupational risk (cases:27% vs. controls:10.6%, p <0.0001) in a higher proportion. Strict lockdown but not sick leave nor telecommuting was the only measure demonstrating protection against COVID-19 (cases:49% vs. controls:70%, p <0.0001). There were no differences in the use of systemic steroids ( p =0.19), immunosuppressants ( p =0.54) or biologics ( p =0.25) between cases and controls. Cases were more often treated with aminosalicylates (45% vs.34%, p =0.022). Having ≥ 1 comorbidities (OR:1.4, 95%CI: 1–1.8), occupational risk (OR:2.05, 95%CI:1.5–2.9) and the use of aminosalicylates (OR:1.4, 95%CI: 1–1.8) were risk factors for COVID-19. On the other hand, the strict lockdown was a protective factor (OR:0.36, CI:0.27–0.48). Conclusion: Comorbidities and epidemiological risk factors are the most relevant aspects for the risk of COVID-19 in IBD patients. This risk of COVID-19 seems to be increased by aminosalicylates but not by immunosuppressants or biologics. The attitude regarding treating IBD patients with aminosalicylates during the COVID-19 pandemic deserves a deeper analysis. Funded by the Carlos III Health Institute COV20/00227.